2018
DOI: 10.1080/20008198.2018.1512263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of posttraumatic stress disorder and depressive symptoms among burn survivors two years after the 2015 Formosa Fun Coast Water Park explosion in Taiwan

Abstract: Background: Posttraumatic stress disorder (PTSD) and depressive symptoms are relatively common in burn survivors. Several previously reported risk factors (e.g. burn severity) have not consistently predicted psychological adjustment post-burn. Empirically-derived risk factors of PTSD from the meta-analysis and theory-derived cognitive variables may be of great predictive value. Objective: This study investigated the prevalence of probable DSM-5 PTSD and major depression (MDD) and the predictors of PTSD and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
1
12
0
3
Order By: Relevance
“…Only two of five studies comparing dissociation with depressive pathology in multivariate models reported significant associations[28,30], a significant difference from the bivariate analysis findings (Fisher’s exact test, P = 0.021). Other problems found to be positively associated with dissociation in sporadic studies included anxiety[34,40,41], somatization[42], adult attention-deficit/hyperactivity disorder[27], general mental health problems[43], increased postdisaster use of alcohol[44] or tobacco[38], suicidality[26], hopelessness[26], anger[41], hostility[45], feeling unsafe[44,46], fear during the disaster[24,47], alexithymia[48], trauma memory disorganization[47], trauma-related rumination[47], maladaptive coping strategies[49], lower academic achievement[27], greater injury-related functional impairment[47], lower health-related quality of life[26], and fibromyalgia syndrome[50]. Dissociation was also associated with early traumatic experience[51] and religiosity[28].…”
Section: Resultsmentioning
confidence: 99%
“…Only two of five studies comparing dissociation with depressive pathology in multivariate models reported significant associations[28,30], a significant difference from the bivariate analysis findings (Fisher’s exact test, P = 0.021). Other problems found to be positively associated with dissociation in sporadic studies included anxiety[34,40,41], somatization[42], adult attention-deficit/hyperactivity disorder[27], general mental health problems[43], increased postdisaster use of alcohol[44] or tobacco[38], suicidality[26], hopelessness[26], anger[41], hostility[45], feeling unsafe[44,46], fear during the disaster[24,47], alexithymia[48], trauma memory disorganization[47], trauma-related rumination[47], maladaptive coping strategies[49], lower academic achievement[27], greater injury-related functional impairment[47], lower health-related quality of life[26], and fibromyalgia syndrome[50]. Dissociation was also associated with early traumatic experience[51] and religiosity[28].…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 37 , 39 , 40 , 46 , 51 , 53 , 59 , 63 Further, in conditions in which there are well-established correlations between certain risk markers and an outcome of interest, such as deranged blood tests on admission and AKI in burn patients, ML yielded highly accurate predictive algorithms. 38 , 44 , 55 24 47 However, attempts to include weakly related risk markers resulted in algorithms that had an overall lower predictive accuracy, rendering them unsafe for clinical practice. This review further identified that some plastic surgery subspecialties, such as hand surgery, have yet to incorporate this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Η θεώρηση της διαδικασίας της ψυχολογικής ανασύνταξης του ατόμου, τόσο μέσα από ένα μοντέλο διάθεσης και στρες, που δίνει έμφαση σε παράγοντες ατομικής ευαλωτότητας, αλλά και μέσα από ένα μοντέλο ελαχιστοποίησης κινδύνου, που δίνει έμφαση στους προστατευτικούς παράγοντες, των οποίων η ύπαρξη θα μειώσει την αρνητική επίδραση της τραυματικής εμπειρίας, αποτελούν εξίσου σημαντικές 'ματιές' στο ψυχικό τραύμα (Rahman, 2017). Σύμφωνα με τους Lazarus & Folkman (1984), τα χαρακτηριστικά της προσωπικότητας επηρεάζουν σημαντικά την αυτό-εκτίμηση του ατόμου, αλλά σε αλληλεπίδραση και με τα ψυχολογικά, γνωστικά και κοινωνικά χαρακτηριστικά, λειτουργούν σαν πηγές καλής διαχείρισης των στρεσογόνων καταστάσεων (Rahman, 2017. Su, 2018.…”
Section: παράγοντες ευαλωτότητας and προστατευτικοί παράγοντεςunclassified
“…Pfeifer & Haeffel, 2014. Άτομα που πίστευαν ότι βιώνουν σοβαρά αρνητικά αποτελέσματα μετά την τραυματική τους εμπειρία, είχαν χειρότερη απόδοση σε κλίμακα ποιότητας ζωής και είχαν περισσότερες πιθανότητες εμφάνισης συμπτωματολογίας μετά-τραυματικού στρες (Leytham & Powell, 2012. Su, 2018.…”
Section: β) τα φυσικά και ιδιοσυγκρασιακά χαρακτηριστικά του ατόμουunclassified
See 1 more Smart Citation